Timber Volume and Weight Tables of Farm-grown Poplar (Populus deltoides Bartr. Ex Marsh.) in Punjab (India) - Dhanda, R. S.; Verma, R. K. (Indian Forester, 2001)
Timber volume and weight tables have been prepared for Poplar P. deltoides, which is an important agroforestry tree species in Punjab and is grown mainly for commercially important industrial timber. Timber volume (both over bark and under bark), fresh timber weight, above ground biomass, and firewood estimate tables have been developed based on regression equations. Of four simple regression models tested for single-entry and multi-entry regression equations, linear and multiplicative models of the form Y = a + bx and Y = a*x ", respectively, provided the best fit to the observed limits of data. Applicability of multi-entry tables was checked through statistical analyses and were found to be applicable without correction. Percentage of bark volume (over bark and under bark timber volume) for clone G-3 was found to be 18.5 and 22.6 per cent, respectively. Tbe specific gravity of green wood came out to be 0.806.